The Review on the Role of Ambiguity of Tolerance and Resilience on Students’ Engagement - Yu, Miao; Wang, Hongliang; Xia, Guoping (Frontiers in Psychology, 2022)
Due to the arrival of positive psychology in the development of teaching, the construct of engagement has been thrived and got a notable function in the educational arena. Alternatively, numerous individual differences, containing ambiguity of tolerance, have been taken into consideration as a result of the key role they can play in the process of learning, and thus, on different facets of the learners’ engagement. Furthermore, resilience is recommended to be an alternate and effective way of engaging EFL (English as a foreign language) learners. Also, it is a significant feature of the human adaptation system in which students can efficaciously manage and tackle stressful involvements despite their troubles and disasters. Given the eminence of both ambiguity tolerance and resilience in educational settings and the fact that little attention has been given to these constructs in foreign language learning, the present review makes an effort to scrutinize the impact of ambiguity of tolerance and resilience on EFL learners’ engagement. Succinctly, the fundamental roles of ambiguity tolerance and resilience in learners’ engagement were confirmed, and consistent with the conclusions drawn from the present review, some suggestions are set forth concerning the implications of this paper.